Reindustrializing Indonesia: Human Capital, Innovation, and Entrepreneurial Growth in a Changing Industrial Landscape - Pramanda, Ryan (Professorline, 2025)
As emerging economies grapple with post-pandemic recovery and long-term development challenges, the call to